Analysis of the approaches used for calculating involute splined couplings and the methods of considering their influence on the dynamic behavior of systems - I. V. Nikolaev; M. K. Leontiev; V. V. Popov (Научный вестник МГТУ ГА, 2023)
Spline couplings, due to their high reliability and strength parameters, are widespread not only in mechanical engineering. The ability to transmit high torque with a sufficiently long service life has led to the extensive use of these couplings in the aircraft industry. Since this unit is under heavy loads in aircraft gas turbine engines, much attention is paid not only to strength characteristics, but also to the influence on the dynamic parameters of the rotor system. To mitigate the risks of destruction and the occurrence of defects, a large number of studies are carried out allowing us to evaluate the rotor system operation with splines and make a forecast of its behavior in the event of various factors leading to a change in the operation of splines. This paper provides a review of various methods, techniques and models of involute spline couplings used in the analysis of the dynamic behavior of rotor systems. The analytical models that allow us to take into account the coupling in various systems as well as finite element models that demonstrate the description of various processes in splines. The publications, devoted to the comparison of finite element models with analytical ones confirming the results associated with the dynamic characteristics of systems with an increase in radial and angular swashes, have been considered. The results of comparing the above models and their results with experimental research to verify and confirm various effects are also presented. The given research of rotor systems with swash allows for a conclusion about a significant spline influence, since they can cause a change in the coupling rigidity, redistribution of contact, increased loads in meshing, increased vibration amplitudes, change in the spectrum of excited frequencies and self-oscillatory processes due to various factors.